HUBUNGAN KOORDINASI DAN KEMAMPUAN APARATUR DENGAN KUALITAS PELAYANAN PUBLIK PADA KANTOR KECAMATAN HALONG KABUPATEN BALANGAN - Erna Suriyani (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
This study aims to determine the relationship of coordination and the ability of the apparatus to the quality of public services at the district office Halong Balangan.This type of research used in this study is the type Eksplanatory, while the approach used is a quantitative approach. To prove the relationship of coordination and the ability of the apparatus to the quality of public services, will be analyzed using Chi Square models. Measuring the quality of care in this study refers to the majority opinion of Parasuraman, Zeithaml, and Berry (Tjiptono, 2004: 132) Levince in Ratminto (2005: 175). Factors affecting the quality of service inferred from Moenir opinion, The Liang Gie Fan Info and theory The Triangle of Service Quality proposed by Morgan and Murgatroyd.The results of this study indicate that coordination with the quality of public services in dimensions realiability and Assurance at the district office Halong district Balangan good level of Significant 1% and 5% proved to be no correlation, while coordination with the quality of public services in the dimension Responsiveness, Empathy, Tangibles at level Significant 1 % proved to be no relationship and the significant level of 5% proved no relationship. While the ability of personnel to the quality of public services in the dimensions of Reliability, Responsiveness, Assurance, Empathy and Tangibles at the district office Halong Balangan at significant level of 1% proved no hungan, while the significant level of 5% proved to be no relationship.Keywords: Quality of Public Services, Coordination and Administrative Capabilities